Pengaruh ITO, NPM, dan DER Terhadap Harga Saham Perusahaan Sektor Barang Baku - Cu, Vanness; Fitriyani, Fitriyani; Wijaya, Trisnadi (Universitas Multi Data Palembang, 2025)
This study aims to determine the effect of inventory turnover, net profit margin and debt to asset ratio on stock prices. This research uses a quantitative approach. The sample was determined by purposive sampling technique, so that 73 samples of raw goods sector companies were obtained during the 5-year period. Hypothesis testing using multiple linear regression analysis. The findings of this study indicate that inventory turnover and net profit margin have an influence on stock prices while debt to asset ratio has no influence on stock prices.